Comparing research investment to United Kingdom institutions and published outputs for tuberculosis, HIV and malaria: a systematic analysis across 1997–2013. Issue 1 (December 2015) - Head, Michael; Fitchett, Joseph; Derrick, Gemma; Wurie, Fatima; Meldrum, Jonathan; Kumari, Nina; Beattie, Benjamin; Counts, Christopher; Atun, Rifat
Abstract Background The "Unfinished Agenda" of infectious diseases is of great importance to policymakers and research funding agencies that require ongoing research evidence on their effective management. Journal publications help effectively share and disseminate research results to inform policy and practice. We assess research investments to United Kingdom institutions in HIV, tuberculosis and malaria, and analyse these by numbers of publications and citations and by disease and type of science. Methods Information on infection-related research investments awarded to United Kingdom institutions across 1997–2010 were sourced from funding agencies and individually categorised by disease and type of science. Publications were sourced from the Scopus database via keyword searches and filtered to include only publications relating to human disease and containing a United Kingdom-based first and/or last author. Data were matched by disease and type of science categories. Investment (United Kingdom pounds) and publications were compared to generate an 'investment per publication' metric; similarly, an 'investment per citation' metric was also developed as a measure of the usefulness of research. Results Total research investment for all three diseases was £1.4 billion, and was greatest for HIV (£651.4 million), followed by malaria (£518.7 million) and tuberculosis (£239.1 million). There were 17, 271 included publications, with 9, 322 for HIV, 4, 451 for malaria, and 3, 498 for tuberculosis. HIV publications received the most citations (254, 949), followed by malaria (148, 559) and tuberculosis (100, 244). According to UK pound per publication, tuberculosis (£50, 691) appeared the most productive for investment, compared to HIV (£61, 971) and malaria (£94, 483). By type of science, public health research was most productive for HIV (£27, 296) and tuberculosis (£22, 273), while phase I–III trials were most productive for malaria (£60, 491). According to UK pound per citation, tuberculosis (£1, 797) was the most productive area for investment, compared to HIV (£2, 265) and malaria (£2, 834). Public health research was the most productive type of science for HIV (£2, 265) and tuberculosis (£1, 797), whereas phase I–III trials were most productive for malaria (£1, 713). Conclusions When comparing total publications and citations with research investment to United Kingdom institutions, tuberculosis research appears to perform best in terms of efficiency. There were more public health-related publications and citations for HIV and tuberculosis than other types of science. These findings demonstrate the diversity of research funding and outputs, and provide new evidence to inform research investment strategies for policymakers, funders, academic institutions, and healthcare organizations.